Examining implicit cognition in people with seizures - Dimaro, Lian (2013)
Background: An estimated 15-30% of individuals referred to epilepsy clinics are diagnosed with non-epileptic attack disorder (NEAD). NEAD is a well-known clinical problem which poses diagnostic and therapeutic challenges to neurological and psychological professionals (Gates & Erdahl, 1993). There are multiple theories on the mechanisms that underlie non-epileptic seizures; however there is limited empirical support for these.